GROUP WORK TO IMPROVE CLASSROOM INTERACTION AND STUDENTSâ SELF-ESTEEM OF STAIN GPA - Wahyuningsih, Sungkawati Kardi (Research And Innovation In Language Learning (RILL), 2018)
This research aimed at observing and describing the process and the results of the action implemented in improving the classroom interaction and the studentsâ self-esteem of STAIN GPA. This research was a classroom action research. The subject of the study is the semester 6 students of English department in the academic year of 2014/2015. The purposive sampling was used in this study. This research consists of three steps, namely: input, transformation, and output. The finding of the research is that the implementation of group work is able to improve the classroom interaction, as they: interaction between student and student, student and teacher, student and learning sources, and student and the environment. In relation to the studentsâ self-esteem, the implementation of group work was able to improve: feeling of competence, feeling to be respected, feeling to be loved, feeling to have a chance for success, and feeling of confidence.